Organic Photovoltaics: On the Study of Exciton Binding Energy with Direct Charge Generation in Photovoltaic Polymers (Adv. Electron. Mater. 11/2016). (November 2016) - Li, Ho‐Wa; Guan, Zhiqiang; Cheng, Yuanhang; Lui, Taili; Yang, Qingdan; Lee, Chun‐Sing; Chen, Song; Tsang, Sai‐Wing
Abstract : Exciton and free‐charge generation processes upon photoexcitation in pristine photovoltaic polymers are investigated and reported by H.‐W. Li et al. in article number 1600200. It is found that there is a clear transition from excitonic to free charge generation with increasing excitation energy. Exciton binding energies and the correspondence with the material dielectric are obtained in a series of conjugated polymers. The results shed light on the understanding of primary charge generation process in organic photovoltaic cells.